2017
DOI: 10.1038/s41598-017-16103-z
|View full text |Cite
|
Sign up to set email alerts
|

Axonemal Lumen Dominates Cytosolic Protein Diffusion inside the Primary Cilium

Abstract: Transport of membrane and cytosolic proteins in primary cilia is thought to depend on intraflagellar transport (IFT) and diffusion. However, the relative contribution and spatial routes of each transport mechanism are largely unknown. Although challenging to decipher, the details of these routes are essential for our understanding of protein transport in primary cilia, a critically affected process in many genetic diseases. By using a high-speed virtual 3D super-resolution microscopy, we have mapped the 3D spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 50 publications
7
41
0
Order By: Relevance
“…For the IFT motor, we determined the transport route for KIF3A-GFP, a component of the heterotrimeric kinesin-2 (KIF3A/KIF3B/KAP) complex that drives anterograde IFT (Engelke et al, 2019, Pazour and Rosenbaum, 2002, Kozminski et al, 1995. In agreement with our previous work in the cilium shaft (Luo et al, 2017), KIF3A was found to have two transport routes at the TZ: an outer route at 92±7 nm along the cilium radius with a route width of 71±17 nm, and an inner route at 0±3 nm along the cilium radius with a 52±2 nm route width (Figure 1 I-K). The IFT cargo α-tubulin-GFP (Hao et al, 2011, Craft et al, 2015 also occupies two distinct transport routes in the TZ: one between the microtubules and ciliary membrane with a radial peak position at 111±1 nm and a route width of 43±3 nm, and the other inside the axonemal lumen with a radial peak position at 0±1 nm and a route width of 98±3 nm (Figure 1 L-N).…”
Section: Speed Microscopy Maps the Transit Routes Of Ciliary Proteinssupporting
confidence: 76%
See 2 more Smart Citations
“…For the IFT motor, we determined the transport route for KIF3A-GFP, a component of the heterotrimeric kinesin-2 (KIF3A/KIF3B/KAP) complex that drives anterograde IFT (Engelke et al, 2019, Pazour and Rosenbaum, 2002, Kozminski et al, 1995. In agreement with our previous work in the cilium shaft (Luo et al, 2017), KIF3A was found to have two transport routes at the TZ: an outer route at 92±7 nm along the cilium radius with a route width of 71±17 nm, and an inner route at 0±3 nm along the cilium radius with a 52±2 nm route width (Figure 1 I-K). The IFT cargo α-tubulin-GFP (Hao et al, 2011, Craft et al, 2015 also occupies two distinct transport routes in the TZ: one between the microtubules and ciliary membrane with a radial peak position at 111±1 nm and a route width of 43±3 nm, and the other inside the axonemal lumen with a radial peak position at 0±1 nm and a route width of 98±3 nm (Figure 1 L-N).…”
Section: Speed Microscopy Maps the Transit Routes Of Ciliary Proteinssupporting
confidence: 76%
“…That the outer transport routes of both KIF3A and a-tubulin localize between the microtubules and ciliary membrane was expected as was the microtubule-proximal localization of the motor as compared to IFT proteins and cargo. We hypothesize that the inner route of both proteins corresponds to a passive diffusion route as we have previously observed in the cilium shaft (Luo et al 2017).…”
Section: Speed Microscopy Maps the Transit Routes Of Ciliary Proteinssupporting
confidence: 58%
See 1 more Smart Citation
“…Species-specific differences are also noted when considering the recycling of the kinesin motors after delivery of IFT particles to the tip of the cilium. In mammalian cilia, kinesin motors have been observed to undergo both retrograde transport and free diffusion back to the cell body [45, 61]. In Chlamydomonas cilia, the kinesin motors do not rely on dynein, rather they return to the base of the cilium by diffusion [51, 58, 62, 81].…”
Section: Discussionmentioning
confidence: 99%
“…Besides IFT, two additional, IFT-independent routes within the lumen of PC are known: passive diffusion and vesicle trafficking (Luo et al, 2017;Ruba et al, 2019).…”
Section: Introductionmentioning
confidence: 99%